ANALISIS KEKUATAN ATAP KUBAH DENGAN STRUKTUR RANGKA KAYU KELAPA - P. Adi Yasa; Decky Cipta Indrashwara (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2023)
The dome roof truss structure with coconut wood is an innovation initiated by CV. Bali Mandala on one of their projects located in Hawaii. Where the main material uses coconut wood which has been treated first to increase termite and fire resistance. This dome roof has a unique floral patterned truss structure, because of this unusual shape of the structure, so to ensure that the structure is safe and can be marketed widely, it is necessary to complete a feasibility test. The limited facilities for direct wind load testing are the reasons why analysis with three-dimensional (3D) computer modeling is needed. To be able to obtain the appropriate structural behavior between reality and the 3D model, validation was carried out by trial and error on the elasticity of the wood to obtain the appropriate deformation between the structure in the field and the 3D model. The validated 3D model is provided with roof loads, wind and snow loads following ASCE 7-22 provisions for the Hawaii area. From the combination of service load (D+Lr) the maximum deformation is 20.7 mm while the maximum allowable deflection is 30 mm. The tensile, compressive, shear, and flexural capacity of wooden elements, is checked based on the Allowable Stress Design Method (ASD) SNI 7973: 2013, where the compressive, tensile, shear, and flexural stresses due to the load are smaller than the allowable stress. So, from the results of stress control and deflection which are still below the limit value, it can be said that the dome roof with the coconut wood frame structure is safe and can be applied.